PENERAPAN ADAPTIVE GOVERNANCE DALAM PENYELENGGARAAN PEMERINTAHAN DI KABUPATEN SIAK TAHUN 2024 - Nurhaliza, Siti; Nisaa, Fadhiilatun (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study analyzes the implementation of Adaptive Governance in the governance of Siak Regency in 2024, focusing on the Smart Governance dimension, specifically the Public Service Mall (MPP) and the Bujang Kampung Program. Using the Adaptive Governance theory of Sharma-Wallace, Velarde, and Wreford (2018), the study emphasizes collaboration, coordination, social capital development, and capacity building. A qualitative descriptive approach was used through interviews and documentation. The results indicate that the implementation of Adaptive Governance has been ongoing but is not yet optimal. Collaboration and coordination between agencies have been established, but are still hampered by uneven understanding and inconsistent attendance at Smart City forums. Social capital is built through satisfaction surveys and direct dialogue with the community, while capacity development remains hampered by limited human resources and budget. Keywords: Adaptive Governance, Smart Governance, Smart City, MPP, Bujang Kampung